The influence of landscape structure on the quality index of surface waters - Fedoniuk Tetyana P.; Fedoniuk Roman H.; Romanchuk Ludmila D.; Petruk Anatolyy A.; Pazych Viktor M. (Journal of Water and Land Development, 2019)
The article focuses on the problem of structure degradation and ecosystem functioning – the urgency that identifies the relevance of operations at a strategic level aimed at providing the integrated assessment of ecological stability of water. Determination of water quality indicators were divided into blocks according to the criteria of salt composition, according to chemical saprobological indicators and the content of specific substances of toxic and radiation action. According to the results of block analysis, the integrated ecological index of water quality was determined by the dependence of water quality on the indicators of ecological stabilization of the landscape and the structure of biotechnical elements. The article determines the relationships between worsening quality of surface waters and stabilization or destabilization of the landscape structure. The research was conducted on medium and large streamflows on the Right Bank of Polesie region of the Dnieper-River cascade within which the tracts of land were identified and the landscape ecological stability (CESL1) and landscape biotechnical elements coefficients (CESL2) were determined. The retrospective analysis was performed of the surface water features on the Right Bank of Polesie region of the Dnieper-River cascade and the main trends in salt block indicators, trophic and saprobiological block indicators, and in the content of toxic and radioactive substances at observation sites were estimated. Based on obtained data, the integrated assessment in trends of surface water quality on the Right Bank of Polesie region of the Dnieper-River cascade was made and the main parameters and scale of stabilization and destabilization of landscape impact on the water quality formation were defined.